2019
DOI: 10.5582/bst.2019.01003
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death ligand-1, tumor infiltrating lymphocytes and HLA expression in Chinese extrahepatic cholangiocarcinoma patients: Possible immunotherapy implications

Abstract: Cholangiocarcinoma (CCA) is a rare cancer biliary tract malignancy which accounts for less than 3% of all gastrointestinal cancers diagnosed worldwide (1). The incidence of CAA is highest in Thailand, China, and other Asian populations, but is lowest in the western world, presumably reflecting differences in the exposure of genetic and other risk factors (2). Anatomically, CCA can be divided into intrahepatic or extrahepatic subtypes choosing second-order bile ducts as the point of separation (3). The majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 50 publications
0
32
1
1
Order By: Relevance
“…The basic characteristics of the eligible studies are shown in Table 1. Seven studies were conducted in China [13,15,16,21,22,27,28], three in Japan [18,24,25], two in Korea [11,20], two in Germany [19,26], two in Germany [14,17], and one in Thailand [23] and UK [12]. One study was of prospective design [12], and 17 were retrospective cohort studies [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The basic characteristics of the eligible studies are shown in Table 1. Seven studies were conducted in China [13,15,16,21,22,27,28], three in Japan [18,24,25], two in Korea [11,20], two in Germany [19,26], two in Germany [14,17], and one in Thailand [23] and UK [12]. One study was of prospective design [12], and 17 were retrospective cohort studies [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis. Seventeen studies [11][12][13][14][16][17][18][19][20][21][22][23][24][25][26][27][28] with a total of 1982 patients reported a correlation between PD-L1 and OS. The pooled HR and 95% CI suggested that overexpression of PD-L1 was significantly correlated with worse OS (HR = 1:58, 95%CI = 1:30 − 1:92, p < 0:001) in patients with CCA ( Figure 2; Table 3).…”
Section: Prognostic Value Of Pd-l1 In Os Dfs and Subgroupmentioning
confidence: 99%
See 3 more Smart Citations